Prediction of the lactation yield in dairy sheep using a test-day animal model, electronic identification of animals and automated data collection - Georgoudis A.; Ligda C.; Gabriilidis G.H.; Papadopoulos T. (Data collection and definition of objectives in sheep and goat breeding programmes: New prospects, 1997)
The purpose of the present paper is to present the data collection and selection scheme of the Chios sheep in the Agricultural Research Station of Chalkidiki. Lambs are evaluated on individual weaning weight and on the dam's performance for milk production and litter size. Furthermore, the prospects of electronic identification of animals and automatic collection of data, combined with the possibilities of earlier selection of lambs, are discussed. Finally, the results of the research concerning test-day records and lactation yield prediction are presented.
Meeting of the FAO-CIHEAM Network of Cooperative Research on Sheep and Goats and Subnetwork on Animal Resources, 9-11 Mar 1997, Toulouse (France)